1981
DOI: 10.1172/jci110349
|View full text |Cite
|
Sign up to set email alerts
|

Ouabain effects on intracellular potassium activity and contractile force in cat papillary muscle.

Abstract: A B S T R A C T The relationship between the positive inotropic and toxic effects of cardiac glycosides and their effects on intracellular ionic composition is incompletely defined. We measured intracellular potassium activity (ak), extracellular potassium activity (at), resting potential, action potential duration, and contractile force at 32°C in paired papillary muscles from feline right ventricles exposed to ouabain. Muscles used for electrophysiological measurements were quiescent except for isolated stim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

1982
1982
1986
1986

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 38 publications
1
3
0
Order By: Relevance
“…The results of the present study demonstrated that ale was indeed different in the infarct and border zone cells. The value of a' in ventricular muscle cells from normal zones was similar to that previously reported for normal cat papillary muscle cells (Browning et al, 1981). In addition, al< in infarct zone cells was similar to that in normal zone cells.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…The results of the present study demonstrated that ale was indeed different in the infarct and border zone cells. The value of a' in ventricular muscle cells from normal zones was similar to that previously reported for normal cat papillary muscle cells (Browning et al, 1981). In addition, al< in infarct zone cells was similar to that in normal zone cells.…”
Section: Discussionsupporting
confidence: 87%
“…In an initial series of three experiments, preparations were exposed to 10~6 ouabain for 60 minutes, using the method of Browning et al (1981). However, all preparations became inexitable within 60 minutes exposure to 10~6 M ouabain, making it difficult to measure ak-In a second series of nine experiments, we lowered the ouabain concentration to 5 X 10" 7 M, and the measurements were made 60 minutes after superfusion with the drug.…”
Section: Effects Of Ouabain On Ai< In Normal Border and Infarct Zonmentioning
confidence: 99%
“…The time-independent potassium conductance also increases and serves as a plausible explanation for the decrease in action potential amplitude (Greenspan & Morad, 1975). Membrane depolarization is observed only with higher concentrations which cause effective pump inhibition and therefore result in substantial intracellular potassium loss (Muller, 1965;Bentfeld, Luillmann, Peters & Proppe, 1977;Browning, Guarnieri & Strauss, 1981). Also, during effective pump inhibition the electrogenic contribution to the membrane potential is diminished (Daut & Rudel, 1982) which causes further depolarization.…”
Section: Discussionmentioning
confidence: 99%
“…Out of nine experiments (sixteen impalements), four experiments (five impalements) met all of these criteria and they are tabulated in Table 1 Because of diffusion of K+ out of the tip of a 3 mol KCI/I electrode it is not possible to use it to fill the reference barrel ofdouble-barrelled electrodes (see Stoner, Natke & Dixon, 1984). In these experiments it was found that neither 1 or 3 mol Li acetate/l or indeed 3 mol Browning, Guarnieri & Strauss (1981) Guinea-pig 37 137…”
Section: Estimation Of [K]i From the Nernst Equationmentioning
confidence: 99%